How are Preservice Early Childhood Professionals' Mindfulness, Reflective Practice Beliefs, and Individual Characteristics Associated with Their Developmentally Supportive Responses to Infants and Toddlers?. Issue 7 (2nd October 2020) - Virmani, Elita Amini; Hatton-Bowers, Holly; Lombardi, Caitlin McPherran; Decker, Kalli B.; King, Elizabeth K.; Plata-Potter, Sandra I.; Vallotton, Claire D.
ABSTRACT: Although the social-emotional competence of preservice early childhood professionals (ECPs) has been associated with the quality of their interactions with young children, there is limited understanding of these associations during preservice training. Utilizing a sample of students with career goals in early childhood ( N = 473), we examined the associations between indicators of preservice ECPs' social-emotional competence (mindfulness and reflective practice beliefs), individual characteristics (depressive symptoms, stressful life events, adverse childhood experiences (ACEs), and attachment security), and endorsing developmentally supportive responses to promote the social-emotional development of infants and toddlers. Research Findings : Preservice ECPs with more stressful life events reported more ACEs and higher depressive symptoms. Stressful life events and ACEs were not significantly correlated with mindfulness or reflective practice beliefs, yet secure attachment style was positively correlated with both of these indicators of social-emotional competence. Depression was significantly and negatively correlated with mindfulness. Ultimately, preservice ECPs with greater reflective practice beliefs endorsed more developmentally appropriate responses. Practice or Policy : Preservice ECPs' reflective practice beliefs may promote practices that support the social emotional development of infants and toddlers once in the workforce.